Sweet potato NAC transcription factor, IbNAC1, upregulates sporamin gene expression by binding the SWRE motif against mechanical wounding and herbivore attack. (18th April 2016) - Chen, Shi‐Peng; Lin, I Winnie; Chen, Xuanyang; Huang, Yin‐Hao; Chang, Shiao‐Chi; Lo, Hui‐Shan; Lu, Hseuh‐Han; Yeh, Kai‐Wun
Summary: Sporamin is a tuberous storage protein with trypsin inhibitory activity in sweet potato ( Ipomoea batatas Lam.), which accounts for 85% of the soluble protein in tubers. It is constitutively expressed in tuberous roots but is expressed in leaves only after wounding. Thus far, its wound‐inducible signal transduction mechanisms remain unclear. In the present work, a 53‐bp DNA region, s poraminw ound‐r esponse cis ‐e lement (SWRE), was identified in the sporamin promoter and was determined to be responsible for the wounding response. Using yeast one‐hybrid screening, a NAC domain protein, IbNAC1, that specifically bound to the 5′‐TACAATATC‐3′ sequence in SWRE was isolated from a cDNA library from wounded leaves. IbNAC1 was constitutively expressed in root tissues and was induced earlier than sporamin following the wounding of leaves. Transgenic sweet potato plants overexpressing IbNAC1 had greatly increased sporamin expression, increased trypsin inhibitory activity, and elevated resistance against Spodoptera litura . We further demonstrated that IbNAC1 has multiple biological functions in the jasmonic acid (JA) response, including the inhibition of root formation, accumulation of anthocyanin, regulation of aging processes, reduction of abiotic tolerance, and overproduction of reactive oxygen species (ROS). Thus, IbNAC1 is a core transcription factor that reprograms the transcriptional response to wounding via the JA‐mediated pathway in sweet potato. Significance Statement: Sporamin is a storage protein with trypsin inhibitor activity, constitutively expressed in tubers but expressed in leaves only upon wounding. Here we show that a NAC transcription factor acts to enhance sporamin expression in leaves in response to wounding and herbivory, via a jasmonic acid‐mediated pathway.